Tingkat keterlibatan kebugaran jasmani dalam peningkatan prestasi belajar PJOK pada siswa: Tingkat Keterlibatan Kebugaran Jasmani Dalam Peningkatan Prestasi Belajar PJOK Pada Siswa - Ramadhan, Muchammad Faishal; Basri, Hasan; Intani, Andini Dwi (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam 45, 2023)
This study aims to determine the contribution of physical fitness to the learning outcomes of sports and health physical education subjects in class v SDN Cengkareng Timur 21 Pagi. This research is a correlation research. The population and sample of this study were 32 students of class V at SDN Cengkareng Timur 21 Pagi with a range of ages 10-12 years. The measurement of the Indonesian Physical Fitness Test is carried out by measuring 5 tests, namely, running 40 meters, hanging your elbows, lying down, jumping upright and running 600 meters. Data collection techniques with tests using the TKJI test form. While the learning achievement data was taken from the grades of the even semester report cards for PJOK subjects. The results showed that the physical fitness test was in the moderate category and the student learning outcomes test was in the good category. This is evident from the normality test of the TKJI data, the value of sig = .200 means that the significance value of the data is greater than 0.05, meaning that the normality test is normally distributed, and the results of the normality test of the Learning Outcomes data are obtained sig = .190, which means the significance value of the data greater than 0.05, it means that the normality test is normally distributed. From the results of the correlation test, it was obtained that the two variables obtained r = .650 included in the sufficient criteria, meaning that there was a significant contribution between physical fitness and student learning outcomes.